Congress volume Zurich 2022: proceedings of the 24th congress of the IOSOT - Arnet, Samuel; Schmid, Konrad; Tiemeyer, Lena-Sofia (Vetus Testamentum / Supplements, 2026)
"This volume presents the main lectures of the 24th Congress of the International Organization for the Study of the Old Testament (IOSOT) held in Zurich, Switzerland, in August 2022. It is written by nineteen established international scholars, whose combined research reflects the broad spectrum of contemporary biblical scholarship. The volume includes articles ranging from the study of the ancient Near East, the archaeology of ancient Israel and Judah, and the Dead Sea Scrolls, via thematic investigations and ideological readings of key texts, to studies exploring the formation, ideology, and reception of biblical books"-- Provided by publisher